1999
DOI: 10.1007/s004230050214
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ultrasonography reliably visualizes bile-duct injuries - a blind randomized porcine study

Abstract: We conclude that laparoscopic ultrasonography can reliably visualize most relevant bile-duct injuries. A standard for doing the ultrasound examination is proposed. Direct and indirect ultrasound signs of bile-duct injuries are explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A prospective multicenter cohort study by Machi et al [51] reported no BDI and only three bile leaks in 1,381 patients. The study of the ability of LUS to detect BDI intraoperatively is limited to two studies in pigs in which it successfully identified wrongfully placed clips and complete transections [56, 57]. …”
Section: Resultsmentioning
confidence: 99%
“…A prospective multicenter cohort study by Machi et al [51] reported no BDI and only three bile leaks in 1,381 patients. The study of the ability of LUS to detect BDI intraoperatively is limited to two studies in pigs in which it successfully identified wrongfully placed clips and complete transections [56, 57]. …”
Section: Resultsmentioning
confidence: 99%